Distance Learning With STEAM Approaches: is the Effect on the Cognitive Domain? - Aminah Zb; Devie Novalian; Rizki Ananda; Mhmd Habibi; Fauzan Sulman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study uses a STEAM approach to learning outcomes of biological innovation, using a quantitative approach with a quasi-experimental method with a posttest-only design with a nonequivalent group design. The population in this study are fourth-semester students of Biology Tadris UIN Sulthan Thaha Saifuddin Jambi, class IVA, IVB, IVC, and VI D, totaling 36 people. Samples were taken using class IVA and IV D with the purposive sampling technique. The instrument in this study was in the form of five essay test questions. Data analysis used t-test and correlation test (phi (Φ)). Analysis of t-test data from the calculation results shows that the use of the STEAM approach is proven to be better than online lectures without using the STEAM approach. The results of the study were continued with a correlation test (phi test (Φ)), from the results of the calculations, it was concluded that the STEAM approach had a significant effect on the learning outcomes of students’ cognitive domains in the biology learning innovation course.Penelitian ini menggunakan pendekatan STEAM terhadap hasil belajar inovasi biologi, menggunakan pendekatan kuantitatif dengan metode kuasi eksperimen dengan desain posttest only dengan nonequivalent group design. Populasi dalam penelitian ini adalah mahasiswa semester IV Biologi Tadris UIN Sulthan Thaha Saifuddin Jambi kelas IVA, IVB, IVC, dan VI D yang berjumlah 36 orang. Sampel yang digunakan adalah kelas VIA dan IV D diambil dengan menggunakan teknik purposive sampling. Instrumen dalam penelitian ini berupa 5 soal tes essay. Analisis data menggunakan uji-t dan uji korelasi (phi (Φ)). Analisis data uji t Dari hasil perhitungan diperoleh kesimpulan bahwa penggunaan pendekatan STEAM terbukti lebih baik daripada perkuliahahan online tanpa menggunakan pendekatan STEAM. Hasil penelitian dilanjutkan dengan uji korelasi (uji phi (Φ)), dari hasil perhitungan diperoleh kesimpulan bahwa pendekatan STEAM berpengaruh signifikan terhadap hasil belajar ranah kognitif mahasiswa pada mata kuliah inovasi pembelajaran biologi.